Leitura de textos de estilo neutro-objetivo: uma proposta pela perspectiva do Círculo de Bakhtin - Silveira, Maristela Schleicher (2021)
The teaching of reading is one of the great challenges of teachers and professors on Basic and Higher education. Realizing that students from SENAI College (Brazilian National Service for Industrial Training) have difficulties understanding through reading, we consider important to develop reading tasks of a discursive genre related to the needs of these undergraduates. The tasks were developed according to Bakhtin Circle theory, since dialogism is the constitutive principle of the statement and, therefore, the meaning is constructed through discursive interaction. The objectives of this study involved a reflection on reading from the Bakhtin Circle and the development of reading exercises from a scientific article. The questions that guided the development of the research were: (1) How the concepts of the reflections of the Bakhtin Circle contribute to the teaching of reading? (2) What reading tasks can be proposed so that academics from higher education courses of technology at SENAI understand objective-neutral texts? We chose as the basis for the development of the questions the article entitled “Integration of IOT and Arduino to assess milk quality: a systematic review.”. Thus, twenty-two questions were elaborated, exploring the scientific reading in a linear manner with a focus on function, construction compositional, and in the sense. In this study, in addition to the questions, comments and expected answers, we present a suggested application of the elaborated script.